Increased expression of interleukin-22 and its receptor is relevant to poor prognosis in laryngeal squamous cell carcinoma: A case control trial. Issue 51 (23rd December 2021) - Ji, Wenjun; Li, Jing; Wang, Xin; Gao, Dongsheng; Zhang, Tiantian
Abstract : Abstract: To detect the expression of interlerukin-22 (IL-22) and associated genes and to evaluate their relationship with clinicopathological features and prognosis in laryngeal squamous cell carcinoma (LSCC). The expression of IL-22 and associated genes were evaluated by immunohistochemistry and real time polymerase chain reaction in LSCC tissues from 30 patients and adjacent non-tumor tissues. A statistical analysis was implemented to assess the relationship among levels of expression, clinicopathological factors, and overall survival. The expression of IL-22 and interleukin 22 receptor 1 (IL-22R1) was mainly located in the cytoplasm, and the expression of LSCC was significantly higher than in controls. The expression of aryl hydrocarbon receptor and signal transducer and activator of transcription 3 distributed in the cell nucleus, which was significantly higher in LSCC than in controls. The expression of IL-22 and IL-22R1 was associated with metastasis of lymph node and clinical stage of LSCC. Overall survival of LSCC was significantly poorer with higher expression of IL-22 and IL-22R1 than in those with lower expression. The present research indicated that the increased level of IL-22 and IL-22R1 may be related to the pathogenesis and prognosis of LSCC. IL-22 may be the important biomarker, which need further research.